Cricoid chondrosarcoma - Rojas, Carolina Sepúlveda (2010)
Chondrosarcoma i a cartilaginous  neoplasm  that  accounts for 1% of malignant tumors. The cricoid cartilage is the most frequent site of onset at the larynx. Signs and symptoms depend on the location of the tumor, which usually presents with hoarseness, dyspnea and dysphagia. TC is the best technique for the diagnosis.The definitive treatment of laryngeal chondrosarcoma is disputable; according to the literature, laryngeal surgery with preservation of function and regular follow up, is the treatment of choice.The histological grade is the most important prognosis factor. We present a case of a chondrosarcoma of the cricoid cartilage of low grade, that was operated in our service.